Enhancement of Corrosion Resistance of Carbon Steel Using Gas Nitriding Technology - Ahmad, Lina Kamilia (IRC, 2018)

(untitled)
Carbon steels are the most extensively used materials throughout oil and gas industry especially for oil and gas pipeline transportation as the steel is low cost and easy to install. However, on exposing to various kinds of corrosive environment, the steels are susceptible to corrosion. This research aims to enhance corrosion resistance, surface hardness as well as examines the microstructure of as-received and nitrided ASTM A106 carbon steel pipe by developing the nitrided surface harden layer using gas nitriding process. High-temperature gas nitriding was employed to treat the steels at 1150 ̊C for various nitriding durations which two until five hours using a constant flow rate of nitrogen gas. Corrosion performance of the samples were tested by using immersion test while Vickers hardness test was used to evaluate the steels surface hardness. Surface characterization techniques such as optical microscopy, Scanning Electron Microscope (SEM), Energy-Dispersive X-ray Spectroscopy (EDX) and X- ray Diffraction (XRD) were also employed to investigate the microstructure, morphology, and compositions of gas nitriding carbon steel. Result obtained shows that the corrosion rate of five hours nitrided carbon steel when compared to the as- received steel has reduced by 22.74% which is from 1.11 mm/yr to 0.86 mm/yr. The surface hardness is approximately three times improved from the untreated sample which the value from 200 HV increases until 600 HV. Meanwhile, the development of the nitriding layer at five hours’ treatment is 171 μm which 13 times thicker than untreated steel that has 13μm thickness. These analyses indicate that nitrided steels provided better corrosion resistance in terms of corrosion rate compared to as-received due to the presence of nitrogen and the denser compound layer at the surface of the steel. The results proved by prolonging the nitriding time diffused more nitrogen into the steel, subsequently, improving the steel’s hardness.